Sharḥ al-arbaʿīn - Qumī, Qāḍī Saʿīd, (Miras Maktoob, ISBN: 9789004365452., 2019)
In the history of Islamic literature, the 'Forty Traditions' genre goes back as far as the 3th/9th century at least and exists in all of Islam's major and minor languages. It finds its origin in the tradition saying that whoever commits forty traditions to memory will be reckoned among the jurists on Resurrection Day. Collections vary, from a simple listing of the basic teachings of Islam to more dedicated works around some specific theme, in either case with or without a commentary. Qāḍī Saʿīd Qumī (d. after 1107/1696) is a Shīʿite philosopher, jurist, physician and mystic of the Safavid period. Having been trained by some of the foremost scholars of his time, he spent most of his active life in Qum, where he divided his time between his judgeship and teaching. The literary, mystical and philosophical explanations in the present, unfinished collection are all written from the viewpoint of the author's own, 'transcendent' metaphysics.